Antistatic composite material and preparation method thereof

By adding modification additives to the ABS material, a composite material with polypyrrole and quaternary ammonium salt structure is formed, which solves the problems of poor anti-static effect and poor high-temperature mechanical performance of ABS material, and achieves a significant improvement in anti-static and mechanical performance.

CN118931101BActive Publication Date: 2025-03-25DONGGUAN ANSHUYI POLYMER MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411252779.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-25
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

At this stage, ABS materials have poor anti-static effects and poor mechanical performance in high-temperature environments, resulting in material damage and electrostatic discharge problems.

Method used

Using a preparation method of antistatic composite material, a composite material with a modified additive is formed by melt extruding ABS masterbatch, modification additive, carbon black and diatompropyl peroxide in a twin screw extruder. The modification additive forms a modifier with polypyrrole and quaternary ammonium salt structure through the reaction of pyrrole derivatives and hydrogen polysiloxane, which enhances the antistatic and mechanical properties of the material.

Benefits of technology

This method significantly improves the antistatic effect and mechanical strength of the composite material, enhances the toughness and heat resistance of the material, and the quaternary ammonium structure of the modified additive can continuously and effectively eliminate static electricity, avoiding the effect reduction due to long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antistatic composite material and a preparation method thereof. The composite material comprises the following raw materials: 80-100 parts of ABS masterbatch, 15-20 parts of a modifying additive, 3-5 parts of carbon black and 0.5-1 parts of dicumyl peroxide. The raw materials are melt-extruded to obtain a composite material. During the extrusion process, under the action of dicumyl peroxide, the double bonds on the modifying additive and ABS molecular chains are grafted to form an interpenetrating grid, thereby improving the mechanical strength of the composite material. Meanwhile, the modifying additive is an elastomer, which can improve the toughness of the composite material. The modifying additive contains an organic silicon segment, which can increase the heat resistance of the composite material. The modifying additive molecular chain contains polypyrrole and a quaternary ammonium salt structure. The quaternary ammonium salt can combine with moisture in the air to form a conductive path, thereby effectively eliminating surface static electricity. The antistatic effect is greatly improved in combination with the carbon black.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antistatic material preparation, and in particular to an antistatic composite material and a preparation method thereof. Background Art

[0002] AcrylonitrileButadieneStyrene copolymers (ABS) is a thermoplastic with good toughness and rigidity. The styrene structure gives ABS good moldability and rigidity; the acrylonitrile structure gives ABS good heat resistance, chemical corrosion resistance and surface hardness; the butadiene structure gives ABS good impact strength and low-temperature resilience. ABS plastics are widely used and are currently commonly used in automobiles, general electrical appliances and other fields. However, since ABS does not have antistatic properties, problems such as demoulding difficulties, dust absorption and electrostatic discharge may occur during processing, transportation and use. Therefore, it is necessary to improve the antistatic properties of ABS resin products, and the high temperature resistance of ABS resin is poor. In a high temperature environment, its own mechanical properties will be greatly reduced, resulting in material damage and affecting normal use. Summary of the invention

[0003] The purpose of the present invention is to provide an antistatic composite material and a preparation method thereof, which solves the problem that the current ABS material has poor antistatic effect and low high-temperature mechanical properties.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing an antistatic composite material comprises the following steps:

[0006] The following raw materials are weighed in parts by weight: 80-100 parts of ABS masterbatch, 15-20 parts of modified additives, 3-5 parts of carbon black and 0.5-1 part of dicumyl peroxide, and the raw materials are added into a twin-screw extruder. Under the conditions that the temperature of zone 1 is 200° C., the temperature of zone 2 is 205° C., the temperature of zone 3 is 210° C. and the temperature of the die head is 205° C., the antistatic composite material is obtained by melt extrusion.

[0007] Further, the modified additive is prepared by the following steps:

[0008] Step A1: dissolving pyrrole in tetrahydrofuran, introducing nitrogen protection, stirring and adding metallic potassium at a speed of 120-150 r / min and a temperature of 68-70° C., reacting for 2-3 hours, cooling to room temperature, adding p-benzoyl chloride, reacting for 20-25 hours, to obtain intermediate 1, mixing intermediate 1, aluminum chloride and DMF uniformly, stirring and adding a modifier at a speed of 120-150 r / min and a temperature of 0-3° C., heating to room temperature, and reacting for 3-5 hours to obtain intermediate 2;

[0009] Step A2: The intermediate 2, dioxane and sodium hydroxide solution are mixed evenly, and reacted for 3-5 hours at a rotation speed of 60-80 r / min and a temperature of 105-110° C. to obtain a pyrrole derivative; the pyrrole derivative, pyrrole, ferric chloride and chloroform are mixed, and reacted for 7-9 hours at a rotation speed of 150-200 r / min and a temperature of 20-25° C.; the mixture is added to ethanol, and the filtrate is removed by filtering; the filter cake is soaked in ammonia water for 5-7 hours, and then washed with deionized water until neutral to obtain a modified additive.

[0010] Furthermore, the amount ratio of pyrrole, tetrahydrofuran, potassium metal and benzoyl chloride in step A1 is 20mmol:6mL:19mmol:18mmol, and the amount ratio of intermediate 1, aluminum chloride, DMF and the carboxyl group on the modifier is 1mmol:6mmol:6mL:3mmol.

[0011] Furthermore, the usage ratio of the intermediate 2, dioxane and sodium hydroxide solution described in step A2 is 1 g:3 mL:3 mL, the concentration of the sodium hydroxide solution is 5 mol / L, and the usage ratio of the pyrrole derivative, pyrrole, ferric chloride and chloroform is 30 mmol:40 mL:1 g:10 mmol.

[0012] Further, the modifier is prepared by the following steps:

[0013] Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 105-110° C. to obtain hydrogen polysiloxane;

[0014] Step B2: 4-(2-oxiranemethoxy)benzonitrile, hydrogen polysiloxane and DMF are mixed evenly, and reacted for 6-8 hours at a speed of 120-150 r / min, a temperature of 60-70°C and a pH value of 11-12 to obtain pretreated polysiloxane; pretreated polysiloxane, methacryloyloxyethyltrimethylammonium chloride, chloroplatinic acid and DMF are mixed evenly, and reacted for 8-10 hours at a speed of 150-200 r / min and a temperature of 70-80°C to obtain modified polysiloxane;

[0015] Step B3: uniformly mix the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 2-3 hours at a speed of 60-80 r / min and a temperature of 75-80°C, add 2,2-bis(hydroxymethyl)propionic acid, react for 2-3 hours, add allyl alcohol, and continue to react for 2-3 hours to obtain a modifier.

[0016] Further, the molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 2:0.4:3:2, and the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.

[0017] Furthermore, the molar ratio of 4-(2-oxiranemethoxy)benzonitrile and hydrogen polysiloxane in step B2 is 4:1, the molar ratio of Si-H bonds on the pretreated polysiloxane and methacryloyloxyethyltrimethylammonium chloride is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of methacryloyloxyethyltrimethylammonium chloride.

[0018] Furthermore, the molar ratio of the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and acryl alcohol described in step B3 is 1:6.5:13:5.2:2, the amount of dibutyltin dioctanoate is 1% of the mass of isophorone diisocyanate, and the molecular weight of polytetrahydrofuran is 1000.

[0019] The beneficial effects of the present invention are as follows: an antistatic composite material disclosed by the present invention comprises the following raw materials: ABS masterbatch, a modifying additive, carbon black and diisopropylbenzene peroxide; the modifying additive is treated with pyrrole as a raw material with benzoyl chloride so that the secondary amine on the pyrrole reacts with the acyl chloride on the benzoyl chloride to obtain an intermediate 1; the intermediate 1 and the modifying agent are introduced into the 3-position of the pyrrole ring of the intermediate 1 under the action of aluminum chloride to obtain an intermediate 2; the intermediate 2 is treated with a sodium hydroxide solution to deprotect the secondary amine to obtain a pyrrole derivative; the pyrrole derivative is reacted with pyrrole to form a polypyrrole structure to obtain the modifying additive.

[0020] The modifier is prepared by ring-opening octamethylcyclotetrasiloxane and tetramethylcyclotetrasiloxane, and then reacting with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to form a hydrogen polysiloxane containing an amino group at the end. 4-(2-oxiranemethoxy)benzonitrile and hydrogen polysiloxane are reacted so that the epoxy group on 4-(2-oxiranemethoxy)benzonitrile reacts with the amino group on hydrogen polysiloxane to obtain a modified polysiloxane. The modified polysiloxane is reacted with methacryloyloxyethyltrimethylammonium chloride so that Si-H on the modified polysiloxane is grafted with a double bond on methacryloyloxyethyltrimethylammonium chloride to obtain a modified polysiloxane. The modified polysiloxane, polytetrahydrofuran and isophorone diisocyanate are reacted, and then the chain is extended with 2,2-bishydroxymethylpropionic acid, and finally the modified agent is capped with allyl alcohol.

[0021] During the extrusion process, under the action of dicumyl peroxide, the double bonds on the modified additive and the ABS molecular chains are grafted to form an interpenetrating grid, which can effectively transmit stress and limit the movement of the ABS molecular chains, thereby improving the mechanical strength of the composite material. At the same time, the modified additive is an elastomer, which can improve the toughness of the composite material, contains an organic silicon segment, and can increase the heat resistance of the composite material. The molecular chain of the modified additive contains polypyrrole and quaternary ammonium salt structures, and the quaternary ammonium salt can combine with moisture in the air to form a conductive path, thereby effectively eliminating surface static electricity, and cooperates with carbon black to greatly improve the antistatic effect, and the effect will not decrease due to long-term use. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0023] A method for preparing an antistatic composite material comprises the following steps:

[0024] The following raw materials were weighed in parts by weight: 80 parts of ABS masterbatch, 15 parts of modified additives, 3 parts of carbon black and 0.5 parts of dicumyl peroxide, and the raw materials were added into a twin-screw extruder. Under the conditions of zone 1 temperature of 200°C, zone 2 temperature of 205°C, zone 3 temperature of 210°C and die head temperature of 205°C, the extruder was melt-extruded to obtain an antistatic composite material.

[0025] The ABS masterbatch model is GN-Ⅱ-0215A.

[0026] The modified additive is prepared by the following steps:

[0027] Step A1: dissolving pyrrole in tetrahydrofuran, introducing nitrogen protection, stirring and adding metallic potassium at a speed of 120 r / min and a temperature of 68° C., reacting for 2 h, cooling to room temperature, adding p-benzoyl chloride, and reacting for 20 h to obtain intermediate 1; mixing intermediate 1, aluminum chloride and DMF uniformly, stirring and adding a modifier at a speed of 120 r / min and a temperature of 0° C., heating to room temperature, and reacting for 3 h to obtain intermediate 2;

[0028] Step A2: Mix the intermediate 2, dioxane and sodium hydroxide solution evenly, react for 3 hours at a speed of 60 r / min and a temperature of 105°C to obtain a pyrrole derivative, mix the pyrrole derivative, pyrrole, ferric chloride and chloroform, react for 7 hours at a speed of 150 r / min and a temperature of 20°C, add to ethanol, filter to remove the filtrate, soak the filter cake in ammonia water for 5 hours, and then wash with deionized water until neutral to obtain a modified additive.

[0029] The amount ratio of pyrrole, tetrahydrofuran, potassium metal and benzoyl chloride in step A1 is 20mmol:6mL:19mmol:18mmol, and the amount ratio of intermediate 1, aluminum chloride, DMF and the carboxyl group on the modifier is 1mmol:6mmol:6mL:3mmol.

[0030] The amount ratio of intermediate 2, dioxane and sodium hydroxide solution described in step A2 is 1g:3mL:3mL, the concentration of sodium hydroxide solution is 5mol / L, and the amount ratio of pyrrole derivative, pyrrole, ferric chloride and chloroform is 30mmol:40mL:1g:10mmol.

[0031] The modifier is prepared by the following steps:

[0032] Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 105° C. for 3 hours to obtain hydrogen polysiloxane;

[0033] Step B2: 4-(2-oxiranemethoxy)benzonitrile, hydrogen polysiloxane and DMF were mixed evenly, and the reaction was carried out for 6 hours at a speed of 120 r / min, a temperature of 60°C and a pH value of 11 to obtain pretreated polysiloxane. The pretreated polysiloxane, methacryloyloxyethyltrimethylammonium chloride, chloroplatinic acid and DMF were mixed evenly, and the reaction was carried out for 8 hours at a speed of 150 r / min and a temperature of 70°C to obtain modified polysiloxane.

[0034] Step B3: uniformly mix the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 2 hours at a speed of 60 r / min and a temperature of 75°C, add 2,2-bis(hydroxymethyl)propionic acid, react for 2 hours, add allyl alcohol, and continue to react for 2 hours to obtain a modifier.

[0035] The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 2:0.4:3:2, and the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.

[0036] The molar ratio of 4-(2-oxiranemethoxy)benzonitrile and hydrogen polysiloxane in step B2 is 4:1, the molar ratio of Si-H bonds on the pretreated polysiloxane and methacryloyloxyethyltrimethylammonium chloride is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of methacryloyloxyethyltrimethylammonium chloride.

[0037] The molar ratio of the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and acryl alcohol described in step B3 is 1:6.5:13:5.2:2, the amount of dibutyltin dioctanoate is 1% of the mass of isophorone diisocyanate, and the molecular weight of polytetrahydrofuran is 1000. Example

[0038] A method for preparing an antistatic composite material comprises the following steps:

[0039] The following raw materials were weighed in parts by weight: 90 parts of ABS masterbatch, 18 parts of modified additives, 4 parts of carbon black and 0.8 parts of dicumyl peroxide, and the raw materials were added into a twin-screw extruder. Under the conditions of zone 1 temperature of 200°C, zone 2 temperature of 205°C, zone 3 temperature of 210°C and die head temperature of 205°C, the extruder was melt-extruded to obtain an antistatic composite material.

[0040] The ABS masterbatch model is GN-Ⅱ-0215A.

[0041] The modified additive is prepared by the following steps:

[0042] Step A1: dissolving pyrrole in tetrahydrofuran, introducing nitrogen protection, stirring and adding metallic potassium at a speed of 120 r / min and a temperature of 70°C, reacting for 2 h, cooling to room temperature, adding p-benzoyl chloride, and reacting for 25 h to obtain intermediate 1; mixing intermediate 1, aluminum chloride and DMF uniformly, stirring and adding a modifier at a speed of 120 r / min and a temperature of 3°C, heating to room temperature, and reacting for 4 h to obtain intermediate 2;

[0043] Step A2: Mix the intermediate 2, dioxane and sodium hydroxide solution evenly, react at a speed of 60 r / min and a temperature of 110°C for 4 hours to obtain a pyrrole derivative, mix the pyrrole derivative, pyrrole, ferric chloride and chloroform, react at a speed of 150 r / min and a temperature of 25°C for 8 hours, add to ethanol, filter to remove the filtrate, soak the filter cake in ammonia water for 6 hours, and then wash with deionized water until neutral to obtain a modified additive.

[0044] The amount ratio of pyrrole, tetrahydrofuran, potassium metal and benzoyl chloride in step A1 is 20mmol:6mL:19mmol:18mmol, and the amount ratio of intermediate 1, aluminum chloride, DMF and the carboxyl group on the modifier is 1mmol:6mmol:6mL:3mmol.

[0045] The amount ratio of intermediate 2, dioxane and sodium hydroxide solution described in step A2 is 1g:3mL:3mL, the concentration of sodium hydroxide solution is 5mol / L, and the amount ratio of pyrrole derivative, pyrrole, ferric chloride and chloroform is 30mmol:40mL:1g:10mmol.

[0046] The modifier is prepared by the following steps:

[0047] Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 150 r / min and a temperature of 110° C. to obtain hydrogen polysiloxane;

[0048] Step B2: 4-(2-oxiranemethoxy)benzonitrile, hydrogen polysiloxane and DMF were mixed evenly, and reacted for 7 hours at a speed of 120 r / min, a temperature of 65°C and a pH value of 12 to obtain pretreated polysiloxane; pretreated polysiloxane, methacryloyloxyethyltrimethylammonium chloride, chloroplatinic acid and DMF were mixed evenly, and reacted for 9 hours at a speed of 150 r / min and a temperature of 75°C to obtain modified polysiloxane;

[0049] Step B3: The modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 60 r / min and a temperature of 80°C. 2,2-bis(hydroxymethyl)propionic acid is added and the reaction is carried out for 2 hours. Allyl alcohol is added and the reaction is continued for 3 hours to obtain a modifier.

[0050] The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 2:0.4:3:2, and the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.

[0051] The molar ratio of 4-(2-oxiranemethoxy)benzonitrile and hydrogen polysiloxane in step B2 is 4:1, the molar ratio of Si-H bonds on the pretreated polysiloxane and methacryloyloxyethyltrimethylammonium chloride is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of methacryloyloxyethyltrimethylammonium chloride.

[0052] The molar ratio of the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and acryl alcohol described in step B3 is 1:6.5:13:5.2:2, the amount of dibutyltin dioctanoate is 1% of the mass of isophorone diisocyanate, and the molecular weight of polytetrahydrofuran is 1000. Example

[0053] A method for preparing an antistatic composite material comprises the following steps:

[0054] The following raw materials were weighed in parts by weight: 100 parts of ABS masterbatch, 20 parts of modified additives, 5 parts of carbon black and 1 part of dicumyl peroxide, and the raw materials were added into a twin-screw extruder. Under the conditions of zone 1 temperature of 200°C, zone 2 temperature of 205°C, zone 3 temperature of 210°C and die head temperature of 205°C, the antistatic composite material was obtained by melt extrusion.

[0055] The ABS masterbatch model is GN-Ⅱ-0215A.

[0056] The modified additive is prepared by the following steps:

[0057] Step A1: dissolving pyrrole in tetrahydrofuran, introducing nitrogen protection, stirring and adding metallic potassium at a speed of 150 r / min and a temperature of 70°C, reacting for 3 hours, cooling to room temperature, adding p-benzoyl chloride, and reacting for 25 hours to obtain intermediate 1; mixing intermediate 1, aluminum chloride and DMF uniformly, stirring and adding a modifier at a speed of 150 r / min and a temperature of 3°C, heating to room temperature, and reacting for 5 hours to obtain intermediate 2;

[0058] Step A2: The intermediate 2, dioxane and sodium hydroxide solution are mixed evenly, and the reaction is carried out at a speed of 80 r / min and a temperature of 110°C for 5 hours to obtain a pyrrole derivative; the pyrrole derivative, pyrrole, ferric chloride and chloroform are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 25°C for 9 hours, and the mixture is added to ethanol, and the filtrate is removed by filtering, and the filter cake is soaked in ammonia water for 7 hours, and then washed with deionized water until neutral to obtain a modified additive.

[0059] The amount ratio of pyrrole, tetrahydrofuran, potassium metal and benzoyl chloride in step A1 is 20mmol:6mL:19mmol:18mmol, and the amount ratio of intermediate 1, aluminum chloride, DMF and the carboxyl group on the modifier is 1mmol:6mmol:6mL:3mmol.

[0060] The amount ratio of intermediate 2, dioxane and sodium hydroxide solution described in step A2 is 1g:3mL:3mL, the concentration of sodium hydroxide solution is 5mol / L, and the amount ratio of pyrrole derivative, pyrrole, ferric chloride and chloroform is 30mmol:40mL:1g:10mmol.

[0061] The modifier is prepared by the following steps:

[0062] Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out at a speed of 200 r / min and a temperature of 110° C. for 5 hours to obtain hydrogen polysiloxane;

[0063] Step B2: 4-(2-oxiranemethoxy)benzonitrile, hydrogen polysiloxane and DMF were mixed evenly, and the mixture was reacted for 8 hours at a speed of 150 r / min, a temperature of 70°C and a pH value of 12 to obtain pretreated polysiloxane; the pretreated polysiloxane, methacryloyloxyethyltrimethylammonium chloride, chloroplatinic acid and DMF were mixed evenly, and the mixture was reacted for 10 hours at a speed of 200 r / min and a temperature of 80°C to obtain modified polysiloxane;

[0064] Step B3: uniformly mix the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 3 hours at a speed of 80 r / min and a temperature of 80°C, add 2,2-bis(hydroxymethyl)propionic acid, react for 3 hours, add allyl alcohol, and continue to react for 3 hours to obtain a modifier.

[0065] The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 2:0.4:3:2, and the amount of dimethyl sulfoxide used is 5‰ of the sum of the mass of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.

[0066] The molar ratio of 4-(2-oxiranemethoxy)benzonitrile and hydrogen polysiloxane in step B2 is 4:1, the molar ratio of Si-H bonds on the pretreated polysiloxane and methacryloyloxyethyltrimethylammonium chloride is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of methacryloyloxyethyltrimethylammonium chloride.

[0067] The molar ratio of the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and acryl alcohol described in step B3 is 1:6.5:13:5.2:2, the amount of dibutyltin dioctanoate is 1% of the mass of isophorone diisocyanate, and the molecular weight of polytetrahydrofuran is 1000.

[0068] Comparative Example 1

[0069] Compared with Example 1, no modified polysiloxane was added in this comparative example, and the remaining steps were the same.

[0070] Comparative Example 2

[0071] Compared with Example 1, this comparative example did not add polytetrahydrofuran, and the remaining steps were the same.

[0072] Comparative Example 3

[0073] Compared with Example 1, no propenol was added in this comparative example, and the remaining steps were the same.

[0074] Comparative Example 4

[0075] Compared with Example 1, this comparative example uses a modifier instead of a modifying additive, and the remaining steps are the same.

[0076] The composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were made into sheets with a diameter of 100 mm and a thickness of 2 mm. The surface resistance was tested at a temperature of 25°C and a humidity of 33%. According to the standard of GB / T1040.1-2018, a 30 mm×5 mm×2 mm specimen was made. The tensile strength was tested at a tensile rate of 5 mm / min. According to the standard of GB / T 1043.1-2008, the pendulum was 7.5 J, the span was 70 mm, and the notch type was A. The impact strength was tested. Then, the sheet was kept warm at 85°C for 5 hours, and the tensile strength and impact strength were tested. The test results are shown in the following table.

[0077]

[0078] It can be seen from the above table that the present invention has good antistatic effect and mechanical strength.

[0079] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an antistatic composite material, characterized in that: The specific steps include: Weigh the following raw materials in parts by weight: 80-100 parts of ABS masterbatch, 15-20 parts of modified additives, 3-5 parts of carbon black and 0.5-1 parts of dicumyl peroxide, add the raw materials into a twin-screw extruder, melt-extrude under the conditions of a zone temperature of 200° C., a zone temperature of 205° C., a zone temperature of 310° C. and a die head temperature of 205° C., to obtain an antistatic composite material; The modified additive is prepared by the following steps: Step A1: dissolving pyrrole in tetrahydrofuran, introducing nitrogen protection, stirring and adding metallic potassium to react, cooling to room temperature, adding p-benzoyl chloride to react, and obtaining intermediate 1; mixing intermediate 1, aluminum chloride and DMF, stirring and adding a modifier, heating to room temperature, and reacting to obtain intermediate 2; Step A2: The intermediate 2, dioxane and sodium hydroxide solution are mixed and reacted to obtain a pyrrole derivative, the pyrrole derivative, pyrrole, ferric chloride and chloroform are mixed and reacted, added to ethanol, filtered to remove the filtrate, soaked the filter cake in ammonia water, soaked, and then washed with deionized water until neutral to obtain a modified additive; The modifier is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted to obtain hydrogen polysiloxane; Step B2: 4-(2-oxiranemethoxy)benzonitrile, hydrogen polysiloxane and DMF are mixed and reacted to obtain pretreated polysiloxane, and the pretreated polysiloxane, methacryloyloxyethyltrimethylammonium chloride, chloroplatinic acid and DMF are mixed and reacted to obtain modified polysiloxane; Step B3: uniformly mix the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react, add 2,2-bis(hydroxymethyl)propionic acid, react, add allyl alcohol, continue the reaction, and obtain a modifier.

2. The method for preparing an antistatic composite material according to claim 1, characterized in that: The amount ratio of pyrrole, tetrahydrofuran, potassium metal and benzoyl chloride in step A1 is 20mmol:6mL:19mmol:18mmol, and the amount ratio of intermediate 1, aluminum chloride, DMF and the carboxyl group on the modifier is 1mmol:6mmol:6mL:3mmol.

3. The method for preparing an antistatic composite material according to claim 1, characterized in that: The amount ratio of the intermediate 2, dioxane and sodium hydroxide solution described in step A2 is 1 g:3 mL:3 mL, and the amount ratio of the pyrrole derivative, pyrrole, ferric chloride and chloroform is 30 mmol:40 mL:1 g:10 mmol.

4. The method for preparing an antistatic composite material according to claim 1, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 2:0.4:3:

2.

5. The method for preparing an antistatic composite material according to claim 1, characterized in that: The molar ratio of 4-(2-oxiranemethoxy)benzonitrile to hydrogen polysiloxane in step B2 is 4:1, and the molar ratio of Si-H bonds on the pretreated polysiloxane to methacryloyloxyethyltrimethylammonium chloride is 1:

1.

6. The method for preparing an antistatic composite material according to claim 1, characterized in that: The molar ratio of the modified polysiloxane, polytetrahydrofuran, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and acryl alcohol described in step B3 is 1:6.5:13:5.2:

2.

7. An antistatic composite material, characterized in that: Prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Antistatic ABS plastic and preparation method thereof

    CN114836000A